Personal and Contextual Antecedents of Knowledge Sharing and Innovative Performance among Engineers. Issue 3 (3rd July 2018) - Abbas, Muhammad; Sajid, Sidra; Mumtaz, Sana
Abstract: This research investigates the impacts of proactiveness, openness to experience, and extraversion on innovative performance among engineers. The work also examines the mediating role of knowledge sharing. Using a person–situation interaction perspective, the study further explores the moderating role of perceived organizational support (POS) in personality–knowledge sharing relationships. Data collected from engineers ( N = 183) across various public and private engineering firms in Pakistan reveal that knowledge sharing mediated the relationship of proactiveness and extraversion with innovative performance. In addition, highly proactive and extraverted engineers are more likely to share knowledge when the POS is high. Contrary to the expectations, engineers who highly exhibit openness to experience are less likely to share knowledge under high POS. These findings provide significant contributions to the theory and practice of engineering management by highlighting the essential link of personality traits with knowledge sharing and innovation among engineers.